A Review of High‐Temperature Foam for Improving Steam Flooding Effect: Mechanism and Application of Foam. Issue 3 (21st January 2022) - Zhao, Fajun; Wang, Kai; Li, Guo; Zhu, Guangmeng; Liu, Lei; Jiang, Yifan
Abstract : With the exploitation of light oil approaching saturation, the exploitation of heavy oil is of particular importance. Thermal recovery technology is typically used in heavy oil recovery, such as steam flooding (SF), steam‐assisted gravity drainage, and cyclic steam stimulation. However, SF technology brings problems such as gravity overlap, viscous fingering, and channeling, reducing the sweep efficiency and oil recovery efficiency. Some studies have proposed that foam and steam should be injected into the reservoir together to plug, turn, and reduce viscosity. Heavy oil production occurs mostly under high‐temperature conditions, which require that the foaming agents have good foaming ability in this environment. The generated foam should have good stability. Meanwhile, the mechanism of steam foam enhancing oil recovery (EOR) also changes. Therefore, the research on the mechanism and application of steam foam technology is discussed. First, the basic theory of foam is introduced, and the research on the mechanism of steam foam EOR is discussed. Second, the application of steam foam in the laboratory and the field is summarized. Finally, the full text is summarized and some prospects are made, to provide some help for future research. Abstract : This article reviews the research progress of high‐temperature foam used to improve the steam flooding effect. This review covers the objectives, which are to: 1) introduce the basic theory of foam, 2) discuss the enhancing oil recovery mechanism of steam foam, 3) summarize the field and laboratory applications of steam foam, and 4) put forward the future development direction.